Genetic relationships of Corynebacterium diphtheriae strains isolated from a diphtheria case and carriers by restriction fragment length polymorphism of rRNA genes Relação genética de cepas de Corynebacterium diphtheriae isoladas de caso e seus contatos por RLFP de rRNA gene - Claudio Tavares Sacchi; Ana Paula Silva de Lemos; Silvana Tadeu Casagrande; Alice Massumi Mori; Carmecy Lopes de Almeida (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
In the present study we report the results of an analysis, based on ribotyping of Corynebacterium diphtheriae intermedius strains isolated from a 9 years old child with clinical diphtheria and his 5 contacts. Quantitative analysis of RFLPs of rRNA was used to determine relatedness of these 7 C.diphtheriae strains providing support data in the diphtheria epidemiology. We have also tested those strains for toxigenicity in vitro by using the Elek's gel diffusion method and in vivo by using cell culture method on cultured monkey kidney cell (VERO cells). The hybridization results revealed that the 5 C.diphtheriae strains isolated from contacts and one isolated from the clinical case (nose case strain) had identical RFLP patterns with all 4 restriction endonucleases used, ribotype B. The genetic distance from this ribotype and ribotype A (throat case strain), that we initially assumed to be responsible for the illness of the patient, was of 0.450 showing poor genetic correlation among these two ribotypes. We found no significant differences concerned to the toxin production by using the cell culture method. In conclusion, the use of RFLPs of rRNA gene was successful in detecting minor differences in closely related toxigenic C.diphtheriae intermedius strains and providing information about genetic relationships among them. No presente estudo, nós reportamos os resultados de uma análise, baseada na ribotipagem de cepas de C. diphtheriae intermedius isoladas de uma criança de 9 anos com difteria e seus 5 contatos. Análise quantitativa por RFLP de rRNA foi usada para determinar a relação destas 7 cepas de C. diphtheriae fornecendo dados de interesse epidemiológico. Nós também testamos estas cepas para toxicidade in vitro usando método de difusão de Elek e in vivo usando método de cultura celular com células VERO. Os resultados de hibridização revelaram que as 5 cepas de C. diphtheriae isoladas dos contatos e uma isolada do caso (cepa isolada do nariz) tiveram padrões idênticos com as 4 enzimas de restrição usadas, ribotipo B. A distância genética deste ribotipo e o ribotipo A (cepa isolada da garganta do caso), que nós inicialmente assumimos ser responsável pela doença do paciente, foi de 0,450 mostrando pouca relação genética entre estes dois ribotipos. Nós não encontramos diferenças relativas à produção de toxina usando método de cultura celular entre as cepas. Em conclusão, o uso de RLFP de rRNA gene foi satisfatório em detectar pequenas diferenças em cepas de C. diphtheriae toxigênicas epidemiologicamente relacionadas e em fornecer informação sobre a relação genética entre elas.